Pembelajaran Kooperatif Sebagai Model Efektif Untuk Mengembangkan Interaksi dan Komunikasi Antara Guru dan Peserta Didik - Nur Indah Rahmawati; Sugeng Sutiarso (Universitas Muhammadiyah Kotabumi, 2019)
Cooperative learning is a model of learning that create the students in a small group. The group formed consist of four to six students and heterogeneous characteristic. The results of examine showed that cooperative learning can be develop interaction and communication between teachers and students, between student and student also. In the other word, cooperative learning very effective to apply in classroom that have less of interaction and communication. Interaction is social activities that have feedback between teacher and student. Communication is procces to convery the message by teacher to the students by using media that create effectiv learning. Cooperative learning that can develop interaction and communication is cooperative learning STAD (Student Team Achievement Division), TPS (Think Pair and Share), TGT (Teams Games and Tournament), and NHT (Numbered Heads Together). In this article explanation the basic reason why cooperative learning can develop interaction and communication?